Pengaruh Edukasi Quartet Card Terhadap Pengetahuan Anak Sekolah Tentang Isi Piringku - Sri Devy Maharani; Yudi Abdul Majid; Puji Setya Rini (Institut Citra Internasional, 2023)
The level of nutritional knowledge of a child is a very important domain for the formation of behavior. Lack of knowledge of children about nutrition resulted in irregular nutritional intake. Therefore, children really need special attention, especially in the level of knowledge about nutrition which is visualized in Isi Piringku. The purpose of this study was to determine the effect of Quartet Card education on school children's knowledge of the contents of Isi Piringku before and after health education. This type of research is quantitative with a pre-experimental method with a one-group pretest posttest approach without a control group. Determination of the sampling technique using cluster random sampling with a target population of 112 students. The research sample is 4th and 5th grade students of SD Negeri 102 Palembang, totaling 88 respondents. The instrument used was a knowledge level questionnaire that was given before and after the Quartet Card educational intervention. Data were analyzed using the Wilcoxon Signed Rank test with a significance level of p value <0.05. The results of statistical tests using the Wilcoxon Signed Rank test showed that the median value before education was 10.00, after education was 14.00, and the p value = 0.000 (p value <0.05). The conclusion of this research is that there is an effect of using Quartet Card education on school children's knowledge about Isi Piringku Contents.